Boundless Economics (Open textbook library., 2013)
This catalog contains educational content originally curated by Boundless. In collaboration with the Boundless team, Lumen Learning imported these OER courses to the Lumen Platform, to ensure they remain freely available to the education community after Boundless ceased operations. Lumen maintains the Boundless content in the same condition it was provided to us. Courses may contain issues with formatting, accessibility, and the degree to which content remains current, accurate, and complete.